Empowering Community through Innovation and Marketing Strategy for Candied Nutmeg Products: A Case Study in Negeri Ureng - Fransisca S Latumahina; Ismail Fanolong; Anisa Rokah Makatita; Astin Habasa; Muhammad Bahri Adi Saputra (Universitas Muhammadiyah Sidoarjo, 2023)
This scientific article presents a case study on the implementation of Real Work Lectures (KKN) in Negeri Ureng, focusing on the innovation and marketing strategy for candied nutmeg products. The goal of this study was to foster empathy and a sense of concern for community issues while promoting the marketability of nutmeg shells through innovative product development. The research employed direct observation methods, particularly in the production of candied nutmeg, involving the local community members who were interested in initiating or expanding their businesses. The results showed that the project provided valuable insights, knowledge, and skills in product innovation using available natural resources in the Ureng Village. Additionally, it assisted local entrepreneurs in enhancing the packaging and branding of their food products to attract consumers. Furthermore, the project facilitated the process of obtaining trading permits, enabling the businesses to gain recognition across various segments of society. The implications of this study emphasize the importance of appropriate marketing strategies to expedite the sale of locally produced nutmeg-based products.Highlight: Innovation and marketability: Promoting the innovative use of nutmeg shells and developing marketable candied nutmeg products. Strategic marketing and packaging: Implementing effective marketing strategies and innovative packaging to enhance sales and expand market reach. Community empowerment: Empowering local producers through fair pricing, facilitating quick sales of processed nutmeg products, and supporting business permit acquisition. Keyword:KKN Implementation, Candied Nutmeg Products, Innovation, Marketing Strategy, Community Empowerment.